Oficina experiências matemáticas: professores e a exploração de padrões - Silva, Renato Silvestre da (2009)
With the objective to verify how activities involving observation of regularities and generalization of patterns are used by teachers in workshops Experiences Mathematics in Schools full-time, was held a qualitative research, using semi-structured interviews with five teachers of these workshops. The relevance of this research is justified by the importance of the work with observation and generalization of patterns, identified by researchers like Mason (1996), Lee (1996) and Vale and Pimentel (2005) as a resource to students express algebraic thinking and create algebraic expressions, giving meaning to the use of symbols. The methodological procedures to prepare the roadmap for research, analyze and implement the protocols were based in the stages of the Didactics Engineering, described by Artigue (1996). The analysis about the present resolutions in the protocols and the recordings that were made during the interviews indicate that these kind of activities are little worked in the workshops Experiences Mathematics, because teachers who give these lessons, know little about why and how work these kind of activities